A new intraoral device to facilitate preparation of the guide plane for removable dental prostheses - Borges, Alexandre Luiz Souto [UNESP]; Borges, Alessandra Buhler; Da Silva, Lucas Hian; Uemura, Eduardo Shigueuki; De Siqueira Ferreira Anzalone Saavedra, Guilherme (My University, 2012)
The design of the ParalAB device facilitates transfer of the path of insertion from the diagnostic cast to the mouth quickly and efficiently.
Keywords: dental surgery; denture; human; instrumentation; prosthesis; tooth occlusion; Dental Abutments; Dental Occlusion; Denture Design; Denture, Partial, Removable; Humans; Prosthesis Fitting; Tooth Preparation, Prosthodontic